Fischer v Unlawful Occupiers: could the court have interpreted the 'may' in section 9(3)(a) of the Housing Act as a 'must' under the circumstances of the case?. Issue 4 (2nd October 2019) - Draga, Lisa; Fick, Sarah
Abstract: In 2017, in the case of Fischer v Unlawful Occupiers, the High Court of South Africa, Western Cape Division, was faced with a legal conundrum. Before it was an application for the eviction of 60 000 desperately poor persons from a number of privately owned properties. Due to the size of the unlawful occupation, the landowners sought an order that the municipality purchase or, alternatively, expropriate their properties. Such expropriation is allowed by s 9(3)(a) of the Housing Act, which provides that a municipality 'may' expropriate land for housing purposes. This article considers whether the court, in Fischer, could have interpreted the 'may' in s 9(3)(a) as a 'must'. This would have enabled it to order the municipality to exercise its powers in terms of s 9(3)(a) to attempt to secure purchase of the land and failing which to expropriate.